2022
DOI: 10.1002/ccd.30327
|View full text |Cite
|
Sign up to set email alerts
|

PRospective REgistry of PAtients in REfractory cardiogenic shock—The PREPARE CardShock registry

Abstract: Aim Cardiogenic shock (CS) is a hemodynamically complex multisystem syndrome associated with persistently high morbidity and mortality. As CS is characterized by progressive failure to provide adequate systemic perfusion, supporting end‐organ perfusion using mechanical circulatory support (MCS) seems intriguing. Since most patients with CS present in the catheterization laboratory, percutaneously implantable systems have the widest adoption in the field. We evaluated feasibility, outcomes, and complications af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The authors report on the use of various MCS, however, they do not compare the different strategies head to head, thus it is difficult to draw conclusions regarding selection of MCS strategies based on this algorithm. Although only a small cohort of patients is reported here, mortality remained around 50% despite receiving MCS, results that are similar to historically reported survival rates for patients with AMI and CS without the use of Impella and extracorporeal membrane oxygenation, thus it is unclear whether this protocol would provide a positive impact on survival 1,2 …”
supporting
confidence: 77%
See 1 more Smart Citation
“…The authors report on the use of various MCS, however, they do not compare the different strategies head to head, thus it is difficult to draw conclusions regarding selection of MCS strategies based on this algorithm. Although only a small cohort of patients is reported here, mortality remained around 50% despite receiving MCS, results that are similar to historically reported survival rates for patients with AMI and CS without the use of Impella and extracorporeal membrane oxygenation, thus it is unclear whether this protocol would provide a positive impact on survival 1,2 …”
supporting
confidence: 77%
“…In this issue, von Lewinski et al reported on the use of a standard operating procedure (SOP) to guide decision‐making in the use of mechanical circulatory support (MCS) in CS. In this report, an SOP using patient characteristics including the need for cardiopulmonary resuscitatoin, age, lactate levels, pH, and predicted response to percutaneous cornary intervention was used to help determine patient appropriateness for MCS and determine the type of support 2 …”
mentioning
confidence: 99%
“…While various decision algorithms have been published to facilitate the selection of patients who might benefit from VA-ECMO [9], hardly any data of adequately powered, prospective, and randomized trials was available [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, baseline characteristics and outcomes may differ between patients that do or do not fulfil ECLS-SHOCK eligibility criteria. [9] is a prospective single center registry, including all patients who underwent cardiac catheterization due to CS at the University Heart Center Graz, Austria, within a consecutive 4-year period from May 2019 to May 2023. At this center, approximately 1200 acute-coronary-syndrome patients are treated per year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation